Application of Monoclonal Antibodies against Bioactive Natural Products: Eastern Blotting and Preparation of Knockout Extract - Hiroyuki Tanaka; Osamu Morinaga; Takuhiro Uto; Shunsuke Fuji; Frederick Asare Aboagye; Nguyen Huu Tung; Xiao Wei Li; Waraporn Putalun; Yukihiro Shoyama (International Journal of Analytical Chemistry)
Matrix-assisted laser desorption/ionization (MALDI) tof mass spectrometry was used for the confirmation of hapten number in synthesized antigen. As application of MAb, the MAbs against ginsenosides and glycyrrhizin have been prepared resulting in the development of two new techniques that we named the eastern blotting method and the knockout extract preparation. In eastern blotting technique, glycosides like ginsenosides and glycyrrhizin separated by silica gel TLC were blotted to PVDF membrane that was treated with a NaIO4 solution followed by BSA resulted in glycoside-BSA conjugate on a PVDF membrane. The blotted spots were stained by MAb. Double staining of eastern blotting for ginsenosides using antiginsenoside Rb1 and Rg1 MAbs promoted complete identification of ginsenosides in Panax species. The immunoaffinity concentration of glycyrrhizin was determined by immunoaffinity column conjugated with antiglycyrrhizin MAb resulting in the glycyrrhizin-knockout extract, which was determined by the synergic effect with glycyrrhizin on NO production using the cell line.